Money supply and inflation in a growing economy: The Nigerian experience - Magnus Okoi Abeng; Idoko Ahmed Itodo; Nwamaka Georgina Nwafor (West African Journal of Monetary and Economic Integration, 2018)
This study revisited the traditional money supply - inflation nexus, presented in Fisher's equation, but relaxed its basic assumption of constant level of output, within the context of the Nigerian economy. The idea was to reveal the level of asymmetry in this relationship under conditions of varying levels of economic growth, at every given level of money supply growth. The study drew inferences from the estimate of a two-regime Threshold Autoregressive Distributed Lag (TARDL) Model, and concluded that, while money supply has positive and statistically significant impact on inflation during periods of "low economic growth", the impact is, however, negative and statistically significant in a regime of "high economic growth".
Keywords: C24; C50; E31; E51 E52; 330; Money Supply; Inflation; Economic Growth; Regime-switching; Threshold Regression